2004
DOI: 10.1534/genetics.104.034843
|View full text |Cite
|
Sign up to set email alerts
|

Deletion Mapping of Homoeologous Group 6-Specific Wheat Expressed Sequence Tags

Abstract: To localize wheat (Triticum aestivum L.) ESTs on chromosomes, 882 homoeologous group 6-specific ESTs were identified by physically mapping 7965 singletons from 37 cDNA libraries on 146 chromosome, arm, and sub-arm aneuploid and deletion stocks. The 882 ESTs were physically mapped to 25 regions (bins) flanked by 23 deletion breakpoints. Of the 5154 restriction fragments detected by 882 ESTs, 2043 (loci) were localized to group 6 chromosomes and 806 were mapped on other chromosome groups. The number of loci mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Large-scale EST sequence comparisons using binmapped wheat ESTs and rice pseudomolecules had previously indicated colinearity between W3 and R1 and between W6 and R2 chromosomes (Sorrells et al 2003; La Rota and Sorrells 2004;Munkvold et al 2004;Randhawa et al 2004). Their centromere homology was confirmed in this study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Large-scale EST sequence comparisons using binmapped wheat ESTs and rice pseudomolecules had previously indicated colinearity between W3 and R1 and between W6 and R2 chromosomes (Sorrells et al 2003; La Rota and Sorrells 2004;Munkvold et al 2004;Randhawa et al 2004). Their centromere homology was confirmed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…W3-R1 and W6-R2 chromosomes and their centromeres have maintained perfect synteny (Figure 3). The remaining wheat and Triticeae chromosomes are associated with linkage blocks corresponding to two or three rice chromosomes (Ahn et al 1993;Gale and Devos 1998;Sorrells et al 2003;Conley et al 2004;Hossain et al 2004;La Rota and Sorrells 2004;Linkiewicz et al 2004;Miftahudin et al 2004;Peng et al 2004;Randhawa et al 2004;Salse et al 2008). Chromosome W1 arose from the fusion of chromosomes with homology to R5 and R10 but its centromere was derived from R5 ( Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…It is these orthologous markers that have then been bin mapped in Lolium/Festuca. The reasons for the absence of genes in the proximal regions of wheat and sorghum could therefore possibly result from (1) only partially representative EST libraries or (2) an inability to detect ESTs as a result of low sequence polymorphism (Sorrells et al 2003 andRandhawa et al 2004 reported between 24 and 45% of loci as monomorphic and therefore that could not be mapped to either nulli-tetrasomic or deletion lines).…”
Section: Discussionmentioning
confidence: 99%
“…BAC DB009O11 had three genes that matched mapped wheat ESTs (BE497888, BE500611 and BE490512). These three ESTs have been mapped to the same co-localized bins (6AL4-0.55-0.90, 6BL5-0.40-1.00, and 6DL5-0.29-0.47) located on the long arm of wheat chromosome 6A, 6B and 6D, respectively Randhawa et al 2004). …”
Section: Analysis Of Non-colinear Genesmentioning
confidence: 99%